2014
DOI: 10.1002/jmv.23917
|View full text |Cite
|
Sign up to set email alerts
|

Early collection of saliva specimens from Bell's palsy patients: Quantitative analysis of HHV-6, HSV-1, and VZV

Abstract: Bell's palsy is the most common cause of facial paralysis. Although it has been associated with diabetes mellitus, hypertension, pregnancy, and preeclampsia, the etiology of Bell's palsy remains unknown. The reactivation of latent herpes simplex virus (HSV) or varicella-zoster virus (VZV) with subsequent inflammation and entrapment of the facial nerve in the narrow labyrinthine segment has been implicated as a cause of facial paralysis, but the active role of these viruses in Bell's palsy is still discussed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
6
25
0
2
Order By: Relevance
“…Causes of unilateral peripheral facial nerve paralysis are various and include idiopathic, viral infection, vascular, autoimmune reactions, traumatic, surgical procedures and neoplastic [11,12]. Herpes viruses seemed to be the most possible infective agent [5,6]. Lower motor neurone (LMN) facial palsy is characterized by unilateral paralysis of all muscles of facial expression for both voluntary and emotional responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Causes of unilateral peripheral facial nerve paralysis are various and include idiopathic, viral infection, vascular, autoimmune reactions, traumatic, surgical procedures and neoplastic [11,12]. Herpes viruses seemed to be the most possible infective agent [5,6]. Lower motor neurone (LMN) facial palsy is characterized by unilateral paralysis of all muscles of facial expression for both voluntary and emotional responses.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids have long been used in Bell's palsy because of their powerful anti-inflammatory effect, and have been proven to be an effective treatment. Studies showed evidence for the presence of herpes simplex virus in some cases of bell's palsy [5,6], thus anti-viral agents were applied in some cases. Approximately 70% of all patients recover completely, and a higher percentage of improvement is achieved if corticosteroid therapy is prescribed [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrates that patients with Bell's palsy have similar HSV and varicella levels, but significantly higher HHV-6 in saliva than controls. In addition, higher HHV-6 levels portend a slower recovery of facial paralysis 12. This evidence points in favour of a link between HHV-6 and Bell's palsy compared with other studied viruses, but more research needs to be performed to confirm these findings.…”
Section: Introductionmentioning
confidence: 90%
“…1). Though HSV-1 is frequently referred as one of the causative agents of this disease [42,43], other viruses, such as the human herpesvirus-6, have also been proposed to be involved in the onset of this form of facial paralysis [44,45].…”
Section: Clinical Manifestations Of Hsv-2mentioning
confidence: 99%